Learning Heat Conductors and Insulators Using Video-Based Learning Media - Sari, Made Ratna Permata; Astawan, I Gede (International Journal of Elementary Education, 2021)
Less material explanation makes learning less effective. Therefore innovation is needed, such as instructional videos, so that learning becomes interesting. The purpose of this study was to produce demonstration-based instructional video media on the topic of conductors and insulators in grade five, whose validity has been tested. This development research uses the 4D model, which consists of four stages: define, design, development, and disseminate. This research trial consisted of two material experts, two media experts, and two practitioners. The research data were collected using a questionnaire method. The instrument used to measure the validity of the media was a rating scale with a scale of 4. The data were analyzed using the mean formula to determine the average score of media validity. The results of the validity of the media in terms of material experts were 3.92, in terms of media experts, it was 3.78, and in terms of practitioners, it was 3.78, with very good criteria. So, the demonstration-based learning video media developed were declared valid.